Comparison of the Effectiveness of Functional, Product, and Geographic Organizational Structures in Global Marketing Strategy - Rehulina Bangun; Benhur Pakpahan; Darmawati (Harmony Management: International Journal of Management Science and Business, 2025)
This study investigates the comparative effectiveness of three primary organizational structures—functional, product-based, and geographic—in facilitating global marketing strategies. Employing a qualitative methodology through in-depth case studies of six multinational corporations across the technology, pharmaceutical, and consumer goods sectors, the research highlights the nuanced interplay between organizational design and strategic marketing execution. Findings indicate that no single structure universally outperforms the others; rather, effectiveness is contingent upon specific contextual factors such as product complexity, market diversity, and the degree of global integration versus local responsiveness required. Functional structures tend to support centralized control and efficiency, while product-based structures enhance innovation and brand focus. Geographic structures, on the other hand, offer adaptability to regional market dynamics. The study underscores the importance of strategic alignment between organizational form and marketing objectives, suggesting that hybrid or flexible configurations may offer optimal outcomes in dynamic global environments. These insights provide actionable guidance for decision-makers in selecting or adapting organizational structures to better support international marketing efforts. Ultimately, the research contributes to a deeper understanding of how structural choices influence global competitiveness and responsiveness, offering a framework for organizational design that aligns with evolving market demands and strategic priorities.